IMPACT OF COVID-19 PANDEMIC ON POSTGRADUATE TRAINEES: WAY FORWARD FOR ACADEMIC ACTIVITIES - Dr. Sadia Hanif (Journal of University Medical & Dental College, 2020)
Mankind has always been facing challenges in form of pandemics which take a lot of lives and spread fear as well [1]. The year 2019 introduced human race with COVID 19 which started from China and in no time spread around the globe [2]. Millions of people got affected and a lot of them had either life threatening complications or lost their lives [2]. Health professionals especially administrators have been under tremendous pressure to meet the needs arising in these unusual circumstances and every department has been getting affected including medical education. Tertiary care teaching hospitals not only cater for the management of patients but also serve the purpose of medical education of various undergraduate and post graduate trainees. When changes made in hospitals specific to pandemic last long they may affect the teaching activities of trainees in number of ways [3]. Most departments in hospitals in developing countries had cut down their manpower and resources to equip the health system in fight against this pandemic especially during the peak time. These measures though inevitable in these difficult times, had an impact on clinical and teaching activities of other departments. Studies done even in developed countries revealed that there was 40 to 80% reduction in training activates of post graduate residents of various departments of hospital [4]. Reason may be temporary attachment to COVID wards, clinics and intensive care units and reduction or cessation of routine outpatients, elective surgeries and teaching activities. COVID 19 had its peak in May-June 2019 in Pakistan and now we may be having a second wave. Hospitals, ICUs, quarantine and isolation centers were full during the first wave and doctors from all the specialties either directly or indirectly got affected by this pandemic [5]. Limited resources forced the hospital administration to attach doctors and health professionals from all the specialties to get attached to covid-19 units in one way or other. Halt in academic and clinical activities of own unit and attachment to a unit in which health professionals have not been trained to may bring a lot of concerns in their minds and may affect their functioning in this difficult time. Due to closure of outpatient departments and diversion of most of the manpower toward COVID-19 patients screening and management; direct and indirect training activities of all the specialty doctors have been affected. Adjusting to this pandemic is need of the hour. At this moment we have to create a nice balance between precautions required to control the pandemic and measures needed to continue medical education for making health professionals more equipped. Smart learning may be a valuable strategy for maintaining the learning curve of residents. Wellness activities centered on increased communication also seem a good option in these difficult times. Teaching programs across the globe had begun to use video-conferencing and the majority planned to continue using this in coming times [6]. It is now high time for academicians to consider utilizing other modes of facilitating learning such as live tele-teaching video conference platforms whereby student’s engagement and interactivity can be preserved, whilst observing appropriate COVID-19 social distancing measures.